Elevated Mean Pulmonary Artery Pressure and Right Ventricular Dysfunction in Children with Chronic Kidney Disease - Peter, Igoche D. (J Cardiovasc Echogr, 2018)
BACKGROUND: Elevated mean pulmonary artery pressure (mPAP) and right heart failure increase mortality in patients with chronic kidney disease (CKD). OBJECTIVES: The objective of this study is to determine the prevalence of elevated mPAP in children with CKD compared with matched controls and to ascertain the relationship between elevated mPAP with right ventricular dysfunction and history of hemodialysis. MATERIALS AND METHODS: A cross-sectional comparative study of mPAP and tricuspid annular plane systolic excursion of 21 children with CKD and age- and sex-matched controls asymptomatic for cardiac disease was conducted. RESULTS: Median mPAP was 27.69 (18.3–36.1) mmHg in CKD patients compared with 14.55 (13.5–17.1) mmHg in controls (P = 0.002). Elevated mPAP was present in 42.9% of CKD group and 0% in controls (P < 0.001). The prevalence of right ventricle (RV) dysfunction in CKD was 9.5% and 0% in controls (P = 0.49). Right ventricular dysfunction was significantly more common in patients with elevated mPAP compared with those with normal mPAP (P < 0.001). Children with CKD who had a history of having been dialyzed were less likely to have elevated mPAP (P < 0.001). CONCLUSION: Elevated mPAP is significantly more common in children with CKD compared with controls. CKD population with mPAP elevation is more likely to have impaired RV function. The occurrence of elevated mPAP was more common in those who were never dialyzed.